The relationship of personality and knowledge sharing - Hummad, Saleha (2015)
Knowledge sharing is a fundamental process of knowledge management. Knowledge sharing may be seen as a set of behaviour by which individuals in an organization voluntarily provide access to their knowledge and experiences. Knowledge sharing of individuals could be influenced by their personality characteristics. Therefore, the aim of this research is to study and enhance the understanding of the relationship of personality traits (namely agreeableness, conscientiousness, extraversion and openness to experience) and knowledge sharing. Questionnaire was used to collect data from the management staff of Engro Fertilizers Limited, Pakistan. The data collected were empirically tested using Pearson’s Correlation via SPSS software. The results of the study show that the personality traits are important individual characteristics that influence knowledge sharing. In this study, agreeableness and openness to experience have been found to have a positive significant relationship with knowledge sharing.